Visualizing the formation of an RNA folding intermediate through a fast highly modular secondary structure switch - Yi Xue (Nature Portfolio, 2016)
Short-lived RNA folding intermediates have important roles in the folding of RNA. Here, the authors combine 15N relaxation dispersion NMR with chemical probing to visualise one of these intermediates, and are able to show it is a secondary structural switch, that might help with folding.